Molecular Subtypes Of Breast Carcinoma And Their Propensity For Lymph-Node Metastasis: A Single-Center Retrospective Analysis From South India - S, Krithesh; Mahadevan, Mahadevan; Anantharamakrishnan, Anantharamakrishnan; T, Amrithraj; Ibrahim, Shahid (Journal of Neonatal Surgery, 2025)
Background: Molecular heterogeneity is evident in the breast carcinoma with consequences for prognosis. Immunohistochemical subtyping, are used to classify the tumors as Luminal A, Luminal B, HER2 enriched and the Triple-Negative Breast Cancer (TNBC). LN metastasis continues to be a powerful prognosticator with possible-subtype specific metastatic propensities. In this retrospective analysis, the distribution of molecular subtypes and their correlation with LN metastasis of patients undergoing MRM was examined. Methods: We reviewed records of 50 female patients treated with MRM for primary breast carcinoma at Chettinad Hospital and Research Institute between January 2023 and December 2024. Data collected included age, tumor size (TNM staging), histological type, molecular subtype (ER, PR, HER2 status), and LN involvement. Statistical analyses employed Chi-square tests and logistic regression via IBM-SPSS v21.0 to evaluate associations, with p < 0.05 denoting significance. Results: The cohort included 36% Luminal A, 28% of Luminal B, 20% HRE2-enriched and 16% TNBC subtypes. Overall, 58% of patients were with LN metastasis. The most common form of metastasis was seen with HER2-enriched (80%) and Luminal B (71%) subtypes, but Luminal A had the least rate of metastasis (33%). Tumor size was highly correlated with nodal involvement (p = 0.001), and for LN metastasis, Luminal B (OR = 3.5, p = 0.02 Conclusion: Our findings confirm a significant association between molecular subtypes and LN metastasis, with HER2-enriched and Luminal B subtypes at elevated risk. Molecular subtyping thus provides valuable prognostic insight, informing tailored surgical and adjuvant strategies. Further multicentric studies with larger cohorts are warranted to validate these results.